THE ANALYSIS OF GRAMMATICAL ERROR MADE BY THE STUDENTS IN WRITING RECOUNT TEXT (A CASE STUDY OF SMA NEGERI 1 PEUSANGAN): THE ANALYSIS OF GRAMMATICAL ERROR MADE BY THE STUDENTS IN WRITING RECOUNT TEXT (A CASE STUDY OF SMA NEGERI 1 PEUSANGAN) - Intan Zuhra (Journal of English Education and Social Science, 2021)
The research of an analysis of grammatical error made by the students in writing recount text has been done at SMAN 1 Peusangan. It was begun from October 2 2020 until October 3 2020. The problem of this research is; What are the most common types of grammatical errors made by the students in writing recount text. Based on the research problem, there is one purpose of the research, namely; to find out the most common types of grammatical errors made by students in writing recount text. The scope of this research focused on the grammatical errors made by 1st grade students of SMAN 1 Peusangan in writing recount text. This research is designed as qualitative research using ‘test’ as the instrument of the research, the data is then analyzed with three steps of procedure, namely: data reduction, data display, and data verification/conclusion drawing. The results of the research on the grammatical errors made by 1st grade students of SMAN 1 Peusangan in writing recount text showed that, capitalization was the most frequent error made by the 1st grade students of SMAN 1 Peusangan with the percentage of 19%, meanwhile run-on sentence was the least frequent error made by the students with the percentage of 0%. Cause of error in intralingual error contributed up to 55% or 165 errors, followed by interference error which contributed up to 35% or 107 errors, and the last is developmental error that contributed up to 10% or 30 errors. Based on the results of research, it was concluded that the 1st grade students of SMAN 1 Peusangan often avoid the systematic of writing without capitalize several types of word like name of place, country, people and also the first letter of a new sentence. Conclusion was stated based on the result that showed capitalization had the biggest contributions on students’ grammatical errors.